2018
DOI: 10.1080/02134748.2017.1385243
|View full text |Cite
|
Sign up to set email alerts
|

Measuring emotional intelligence in Moroccan Arabic: the Wong and Law Emotional Intelligence Scale / Medidas de la inteligencia emocional en árabe marroquí: la escala de inteligencia emocional de Wong y Law

Abstract: Emotional intelligence is a widespread concept that has been analysed in different countries. However, it has been barely measured in African-Arab societies' cultures due to their scarce tradition in validating instruments. In Morocco, the mere translation of instruments is a common practice that should be avoided to incorporate cultural and linguistic singularities. Thus, the aim of our study was to culturally adapt the Wong and Law Emotional Intelligence Scale to Morocco. This version could be widely used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
11
0
4
Order By: Relevance
“…However, its use has spread to other contexts in which relationships occur (Lopez-Zafra and Gartzia, 2014). For example, it has been successfully adapted and used with Moroccan women by El Ghoudani et al (2018). We use this adaptation to analyze its usefulness with Moroccan adolescents but further revise it for use among adolescents (see procedure above).…”
Section: Methodsmentioning
confidence: 99%
“…However, its use has spread to other contexts in which relationships occur (Lopez-Zafra and Gartzia, 2014). For example, it has been successfully adapted and used with Moroccan women by El Ghoudani et al (2018). We use this adaptation to analyze its usefulness with Moroccan adolescents but further revise it for use among adolescents (see procedure above).…”
Section: Methodsmentioning
confidence: 99%
“…The authors initially proposed this instrument for the study of EI in the workplace. However, its use has spread to other contexts [3], [7], [13]. The WLEIS is considered a short instrument, comprising 16 items that are scored on a seven-point Likert scale (1 _totally disagree to 7 _ totally agree) [7].…”
Section: B Questionnairementioning
confidence: 99%
“…Several studies assessed the EI in Arabic Countries into both perspectives: the trait and or ability [3], [10], [13], [23] - [27]. In Lebanon, the role of emotions in the formation of young students has been scarcely studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the world, psychometric studies have been carried out on the WEIS using different samples. Results have found that, by-in-large, the instrument is made up of the four originally-proposed dimensions (Carvalho, Guerrero, Chambel, & González-Rico, 2016;El Ghoudani, Pulido-Martos, & Lopez-Zafra, 2018;Fukuda, Saklofske, Tamaoka, & Lim, 2012;Iliceto & Fino, 2017;Nguyen, Nham, & Takahashi, 2019;Pacheco, Rey, & Sánchez-Álvarez, 2019); however, studies are scarce for Latin American (Merino Soto, Lunahuaná-Rosales, & Pradhan, 2016). Additionally, there is a lack of knowledge regarding the psychometric properties of WLEIS with samples that involve workers in general and managers specifically.…”
Section: Regulation Of Emotionmentioning
confidence: 99%